Numerical investigation of heat transfer enhancement via dimpled target surface configuration and jet arrangement in impingement cooling - Mohd Zulkeple, Muhammad Fitri; Abu Talib, Abd Rahim; Harmin, Mohammad Yazdi; Saadon, Syamimi; Azami, Muhammad Hanafi; Yusaf, Talal (Aeronautical and Astronautical Society of the Republic of China, Taiwan, 2024)
This research employs numerical simulation to investigate the influence of dimple configurations on heat transfer. Specifically, it focuses on the 3x3 array of jets directed at a dimpled target surface. The study explores various jet pitches (P = 3D_j, 4D_j and 5D_j) and distances between jets and the dimpled surface (H = 3D_j, 4D_j and 5D_j). Additionally, dimple designs were altered while keeping their volume constant, resulting in elongated dimples. This investigation comprehensively examines flow patterns and heat transfer properties across Reynolds number (Re) range of 5,000 to 15,000. Increasing the H/D_j ratio from 4 to 5 enlarges entrainment vortices near the target surface due to reduced cross flow intensity between adjacent jets. Conversely, reducing the ratio to 3 intensifies crossflow, delaying cooling jet detachment and enhancing heat transfer. Evaluating the smallest jet-to-jet pitch (P_x = 3D_j) reveals enhanced heat transfer to the target surface, driven by increased coolant mass flow rate per unit area compared to larger jet pitches (P_x = 4D_j and P_x = 5D_j). When altering dimple depths while maintaining constant volume, Nusselt numbers (Nu) showed improvements ranging from 10% to 16%, surpassing the 6% to 14% increase seen with hemisphere dimples.